Regional Logistics In The Framework Of State Defense And Improving Regional Economic Development - Aris Doni Sulistiono; Veithzal Rivai Zainal; Aziz Hakim (Dinasti Publisher, 2023)
The essence of administering the state is ensuring the survival of the nation and state within the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution, so the implementation of state defense is organized in a universal defense system involving all citizens, territories and other national resources that are prepared early. by the government and carried out in a total, integrated, directed and continuous manner to uphold state sovereignty, territorial sovereignty and the safety of the entire nation from all threats. The Universal People's Defense System is basically an embodiment of the deployment of the totality of national potential and resources against forces that threaten the survival of the nation. This condition is a common condition that occurs in any nation when the survival of that nation is threatened. During the war for independence, all natural resources, one of which was food potential, made a very large contribution to support the implementation of national defense.In dealing with military threats, the national defense system places the Indonesian National Armed Forces (TNI) as the Main Component, supported by reserve components and supporting components. Meanwhile, in dealing with non-military threats, ministries/agencies other than the defense sector are placed as the main element, in accordance with the form and nature of the threats faced, supported by other elements of national strength. In order to build preparedness of natural and man-made resources which directly or indirectly increase the strength and capability of the Main Components and Reserve Components of the Ministry of Defense as the leading sector in the logistics sector for national defense areas, carry out the development of the Food Estate program which examines several potential land locations for planting strategic commodities. The plan to develop the